EXPERIENCE OF PERFUSION RECELLULARIZATION OF BIOLOGICAL LUNG SCAFFOLD IN RATS - E. V. Kuevda; E. A. Gubareva; A. S. Sotnichenko; I. S. Gumenyuk; I. V. Gilevich; I. S. Polyakov; V. A. Porhanov; S. N. Alekseenko; P. Macchiarini (Вестник трансплантологии и искусственных органов, 2016)
Aim. The main aim of our research is to evaluate the process of rat lung decellularization and recellularization as the initial step of tissue-engineered organs creation.Materials and methods. Rat lung decellularization was performed by perfusion with detergents and enzymes with concomitant atmospheric air ventilation through the trachea. The quality of decellularization was analyzed with routine histological and immunohistochemical staining techniques, DNA content was determined quantitatively by spectrophotometer. For static and whole organ reseeding as a model of cells’ behavior mesenchymal multipotent stromal cells were used. Recellularization was followed by assessment of the cellular metabolic activity by colorimetric method; cell viability was analyzed by calcein and ethidium homodimer staining. Matrix qualitative evaluation after recellularization was performed using immunohistochemical staining methods.Results. 92% of allogeneic DNA was eliminated after decellularization. Histological staining revealed no residual cells and cell nuclei; preservation of the fibers of extracellular matrix was confirmed by immunohistochemical staining for laminin, elastin, fibronectin, collagen types I and IV before and after decellularization. The scaffold does not exhibit toxic properties after reseeding; cell viability and metabolic activity were proved after cultivation.Conclusion. The experience of rat lung decellularization and recellularization can be the prospective basis for protocols of organ recellularization and tissue engineered lungs creation.